Genome-wide analysis of the S-phase kinase-association protein 1 (ClSKP1) family and the role of S-RNase targeting by an SCF (Cullin1-SKP1-F-box) complex in the self-incompatibility of ‘Xiangshui’ lemon - Yuze Li; Wei Lin; Jiawei Zhu; Moying Lan; Cong Luo; Yili Zhang; Rongzhen Liang; Liming Xia; Wangli Hu; Xiao Mo; Guixiang Huang; Xinhua He (Horticultural Plant Journal, 2025)
The SKP1 gene is an important component of the SCF (SKP1-Cullin1-F-box) complex and serves as a bridge connecting the F-box and Cullin1 genes (F-box-SKP1-Cullin1). The pattern of S-RNase being ubiquitously labelled by the SCF complex and degraded by the 26S protease accounts for the bulk of the available self-incompatibility studies. In this study, 15 ClSKP1s from the ‘Xiangshui’ lemon genome and ubiquitome exist in the same SKP1 conserved domain (CD) as SKP1s in other species. The qPCR results showed that SKP1-6 and SKP1-14 have tissue expression patterns specific for expression in pollen. In addition, SKP1-6 and SKP1-14 in the stigma, style and ovary were significantly upregulated after self-pollination compared to those after cross-pollination. A subcellular location showed that SKP1-6 and SKP1-14 were located in the nucleus. In addition, yeast two-hybrid (Y2H) assays, bimolecular fluorescence complementation (BiFC) and luciferase complementation imaging (LCI) assays showed that SKP1-6 interacted with F-box1, F-box33, F-box34, F-box17, F-box19, Cullin1-2 and 26S proteasome subunit 4 homolog A (26S PS4HA). SKP1-14 interacted with F-box17, F-box19, F-box35, Cullin1-2 and 26S PS4HA. The interaction of Cullin1-2 and the F-box with SKP1 as a bridge was verified by a yeast three-hybrid experiment. The ability of S3-RNase to inhibit pollen and pollen tube growth and development was assessed using in vitro pollen co-culture experiments with recombinant S3-RNase proteins. Overall, this study provides important experimental evidence and theoretical basis for understanding the mechanism of self-incompatibility in plants by revealing the key role of the SCF complex in ‘Xiangshui’ lemon, which is bridged by ClSKP1-6, in self-incompatibility. The results of this study are of great significance for the future in-depth exploration of the molecular mechanism of the SCF complex and its wide application in the self-incompatibility of plants.